Tratamento de efluente oriundo da produção de protetor solar - Bosa, Bernardo Bonavigo (2022)
Effluents from cosmetics manufacturing have two peculiar characteristics when compared to other industrial effluents, besides being pollutants due to their high chemical load, effluents from cosmetics manufacturing are very difficult to treat due to their high cost. As it is a market in constant expansion, industries are always looking for new technologies, many of these effluents do not have an adequate treatment and thus can present unpredictable problems when treated. The use of the Reverse Osmosis method for this case is due to its high capacity to remove micropollutants without increasing the amount of unwanted by-products, making the process simpler and closer to the desired results, besides removing colloids in the effluent, making it clearer again. We will discuss the treatment of the effluent from the production of sunscreens in a cosmetics company. The effluent has a whitish color, with high turbidity, total chlorides, and an extremely high COD. Therefore, it will be used the process of separation by reverse Osmosis to the effluent in two pressure situations, at 100 and 150 psi and after collected its permeate to then seek through physical-chemical treatments a decrease in these parameters in order to be able to return it to water resources or even fit into some kind of reuse within the industry. The tests performed with Reverse Osmosis presented an excellent removal of the parameters analyzed, while the coagulation with a concentration of 5 mg/L of PAC 18% for the physicochemical test also presented an excellent reduction in some of the parameters analyzed, while others were not so efficient, being Cor from 365 HZ of the crude reduced to 5 HZ at the 100 psi pressure, totaling a 99% reduction and 10 HZ for the 150 psi pressure, totaling 97% reduction in the OI trials while the physicochemical showed an index of 65 HZ giving an 82% reduction. The initial 391 NTU turbidity of the crude reduced to 0 NTU at 100 psi pressure, with a 100% reduction, and for the 150 psi pressure it presented an index of 1.01 NTU, with a 99% reduction. As for the physicochemical one, it presented an index of 28 NTU, a reduction of 93%. The Organic Matter parameter (mg/L) for the raw effluent characterized with a concentration of 777.03 mg/L, after the OI test presented a concentration of 77.49 mg/L for both pressures, totaling a reduction of 90%. The physicochemical treatment presented a reduction to 759.83 mg/L of Organic Matter, totalizing only 2% of removal. The Phenolics parameter (mg/L) presented an index of 78.83 mg/L for the crude, and after the OI tests for the 100 psi pressure we obtained a 7 value of 12.96 mg/L, totaling a reduction of 84%, while for the 150 psi pressure we obtained a value of 5.4 mg/L totaling a reduction of 93%. The physical-chemical treatment presented a concentration of 3.24 mg/L, an efficacy of 96%. The Total Dissolved Solids (mg/L) of the crude presented a concentration of 996 mg/L and after the OI test for the 100 psi pressure we obtained 100% removal of solids, while for the 150 psi pressure we obtained a concentration of 20 mg/L, totaling a 98% reduction. The physicochemical test showed a concentration of 576 mg/L of Solids, an efficiency of 42%. The Electrical Conductivity (μS/cm) of the raw effluent showed an index of 741.79 μS/cm and after the reverse osmosis tests were done, for the pressure of 100 psi it showed a value of 13 μS/cm and for the pressure of 150 psi it showed a value of 14 μS/cm, totaling a salt retention of 98%. The physicochemical test showed an index of 628 μS/cm, a low efficiency of only 15% reduction. The pH levels remained in an optimal range, since the raw effluent presented a pH of 4.84 where the physicochemical presented a pH of 7.99 while the OI permeates, for the 100 psi pressure presented a pH of 8.52 and for the 150 psi pressure presented a pH of 6.85, thus, it is not necessary to perform correction of the pH levels.